Negative perfectionism and sleep quality in Chinese international students under COVID-19 epidemic: A moderated mediation - Zhaoyang, Huang; Feng, Chen; Mei, Fan; Jingjing, Lin; Jiyang, Pan (Frontiers in Psychology, 2022)
Objective This study used a moderated mediation model to test the mediating effect of anxiety on the relationship between negative perfectionism and sleep quality and the moderating effect of COVID-19 epidemic risk perception during the COVID-19 pandemic in Chinese international students. Methods A sample of 239 Chinese international students from the south of China, was surveyed with the Negative and Positive Perfectionism Scale, the Pittsburgh Sleep Quality Index, the General Anxiety Disorder Scale, and the COVID-19 Epidemic Risk Perception Inventory. SPSS (23 version) and PROCESS (3.3 model 14) were used for correlation analyses, mediation analysis, and moderated mediation analysis. Results (1) Negative perfectionism was significantly correlated with anxiety (r=0.371, p<0.01) and sleep quality (r=0.291, p<0.01); anxiety was significantly correlated with sleep quality (r=0.594, p<0.01). (2) The mediating effect test showed that anxiety had a completed mediating effect between negative perfectionism and sleep quality (β=0.157, p<0.01). (3) Epidemic risk perception moderated the mediating effect of anxiety between negative perfectionism and sleep quality (β=0.070, p<0.01). Conclusion Negative perfectionism affected sleep quality indirectly through anxiety. In particular, COVID-19 epidemic risk perception moderated the relationship between anxiety and sleep quality, such that the association was stronger when the COVID-19 epidemic risk perception was high. These results provide a more comprehensive understanding of the negative link between negative perception and sleep quality.